1996
DOI: 10.1001/archsurg.1996.01430130046008
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Calmodulin Regulate Lipopolysaccharide-Induced Alveolar Macrophage Production of Tumor Necrosis Factor and Procoagulant Activity

Abstract: Our results indicate that increased intracellular calcium causing signal transduction activation through the calmodulin pathway is a necessary, but insufficient, component of the LPS signaling in M phi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…However, it did optimize the M response to subsequent inflammatory stimuli. A23187 augmented TNF and PCA production by LPSstimulated M [14]. In this study, A23187 had no effect on IL-10 inhibition of either TNF or PCA production which suggests that IL-10 has no effects on calcium flux from either the extracellular or the endoplasmic reticular sources.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…However, it did optimize the M response to subsequent inflammatory stimuli. A23187 augmented TNF and PCA production by LPSstimulated M [14]. In this study, A23187 had no effect on IL-10 inhibition of either TNF or PCA production which suggests that IL-10 has no effects on calcium flux from either the extracellular or the endoplasmic reticular sources.…”
Section: Discussionmentioning
confidence: 46%
“…Our recent study suggested that the production of both TNF and PCA by LPSstimulated M was also regulated by PLC pathways [14]. PLC hydrolyzes membrane phospholipids to release IP 3 and DAG, leading to an increase in [Ca 2ϩ ] i and protein kinase C activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, EDTA abrogates the enhancement of LPS-induced TNF-␣ production by HBP (18). Furthermore, the depleting effect of EDTA on Ca 2ϩ is a possible reason for the lower responses to LPS obtained in EDTA blood because a Ca 2ϩ dependence of the LPS-induced TNF-␣ response of alveolar (19) and peritoneal (20) macrophages from rabbits and mice has been demonstrated previously.…”
Section: Discussionmentioning
confidence: 91%
“…Priming/activation sequence is frequently observed in patients with multiple organ failure [21]. When two or more seemingly trivial insults occur on MØ, a synergistic effect is observed [22]. Others often cite the hypothesis of priming and activation mechanism as an explanation for the enhanced production of pro-inflammatory cytokines or up-regulation of pro-inflammatory genes observed in many clinical observations, including ischemia and reperfusion injury; our study further suggests that priming and activation also occurs in the regulation of anti-inflammatory mediators such as PGE 2 .…”
Section: Discussionmentioning
confidence: 99%